2018
DOI: 10.1002/ags3.12212
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and prognostic implication of albumin‐bilirubin‐TNM score in Child‐Pugh class A hepatocellular carcinoma

Abstract: Background and AimA reliable classification for predicting postoperative prognosis and perioperative risk of hepatocellular carcinoma (HCC) patients is required to make a precise decision for HCC treatment. In the present study, we assessed the perioperative and prognostic importance of indocyanine green (ICG) testing, tumor‐node‐metastasis (TNM) stage, albumin‐bilirubin (ALBI) grade, and ALBI‐TNM (ALBI‐T) score using consecutive resected HCC cases.MethodsBetween 1998 and 2011, 273 consecutive patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
1
13
2
Order By: Relevance
“…The score has been validated in hepatic and nonhepatic, elective, and emergency surgeries for short-term as well as long-term outcome prediction [23][24][25]. There is enough evidence that elective surgery is safe and feasible in patients with Child-Pugh class A cirrhosis who have preserved liver function [26,27]. Child-Pugh class B and C patients are at high risk of perioperative outcomes, and some authors consider this as a relative contraindication to surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The score has been validated in hepatic and nonhepatic, elective, and emergency surgeries for short-term as well as long-term outcome prediction [23][24][25]. There is enough evidence that elective surgery is safe and feasible in patients with Child-Pugh class A cirrhosis who have preserved liver function [26,27]. Child-Pugh class B and C patients are at high risk of perioperative outcomes, and some authors consider this as a relative contraindication to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Child-Pugh class B and C patients are at high risk of perioperative outcomes, and some authors consider this as a relative contraindication to surgery. In a study including 273 patients, Sonohara et al [26] reported clinical data on 235 patients who were all Child-Pugh class A. In a multicenter study including 253 patients with Child-Pugh class B cirrhosis from 14 international centers, Berardi et al [28] have shown that postoperative morbidity following HR in these patients remains high (42.7%).…”
Section: Discussionmentioning
confidence: 99%
“…22 The ALBI grade was proposed as a simple and objective method for assessment of liver function in HCC as a result of an international collaborative study. 23 Although ALBI grade has been validated externally in several other studies, 7,8,24,25 it does not incorporate portal hypertension or liver fibrosis. Therefore, blood platelet count was introduced as a surrogate marker of portal hypertension to develop the PALBI grade.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a robust association of albumin–bilirubin and tumor–node–metastasis (TNM) score with perioperative risks and postoperative patient survival . A recent model for hepatic functional reserve based on albumin–bilirubin (ALBI) grade, platelet–albumin–bilirubin (PALBI) grade, can be potentially used to evaluate liver fibrosis status as well as hepatic reserves because the model includes a platelet component, which is an established indicator for liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation